Perbandingan Urutan Item Tes Daya Tahan Otot Tungkai Berdasarkan Sumber Energi - Juniadi, Raafi Rizky; Imanudin, Iman; Umaran, Unun; Subarjah , Herman (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2024)
This research aims to provide trainers with an understanding of the preparation of test items and measurement of physical condition based on physiological principles by comparing the results of leg muscle endurance tests carried out at the end and at the beginning. The method used is one group pretest-posttest design using an experimental design and quantitative approach. Using SPSS 25, data analysis procedures include normality testing, descriptive statistics, and hypothesis testing. The results obtained from testing using average values, data analysis and hypothesis testing resulted in the finding that the test carried out at the end was more effective, namely 53.90 and the test value at the beginning was 32.35. With a significant value (2-tailed) of 0.000 < 0.05 obtained from hypothesis testing, it can be concluded that Hα is accepted and Ho is rejected. Based on computational findings and descriptive statistical values of the test at the end and the test at thebeginning, it can be concluded that there is a comparison of the order of leg muscle endurance test items based on energy source.